Analysis of Genetic Diversity and Core Germplasm Construction of Castanea crenata Siebold and Zucc. Using Simple Sequence Repeat Markers and Morphological Traits - Yanhong Cui; Xinghua Nie; Juanjuan Liu; Shihui Chu; Hanqi Liu; Kaiyuan Xu; Yi Shao; Zhannan Wang; Ruijie Zheng; Yu Xing (Plants)
This study investigates the taxonomic status, phylogenetic relationships, and genetic diversity of Japanese chestnut (Castanea crenata Siebold & Zucc.) in Liaodong, China, and across East Asia. Additionally, it evaluates core germplasm resources through cluster and population structure analyses using simple sequence repeat (SSR) marker data from 13 Castanea henryi, 18 Castanea seguinii, and 27 Castanea mollissima, and 142 Japanese chestnut resources. The results show that the East Asian Castanea genus forms a monophyletic group with distinct interspecific boundaries. Japanese chestnut and two varieties/lines of C. seguinii (187 and 170) form a sister clade, indicating a close phylogenetic relationship. All Japanese chestnut resources are divided into two branches, with considerable admixture. The genetic diversity analysis revealed that the 142 Japanese chestnut varieties/lines collectively possessed 141 allelic loci, with genetic distances (GDs) ranging from 0.429 to 0.880 with an average of 0.740. Based on unique characteristics, seven resources with distinctive features were selected as mandatory. A total of 41 core germplasm resources were finally determined using the simulated annealing method. The comparative analysis revealed that, aside from a notable difference in polymorphic information loci, the core germplasm and original germplasm showed no significant differences in other genetic diversity parameters. This indicates that the 41 core germplasm resources effectively preserve the genetic diversity of the original germplasm and have been influenced by artificial selection. This study provides a scientific basis for conserving and using C. crenata germplasm resources.